THE INFLUENCE OF HIGH SCHOOL STUDENTS’ COMMUNICATION WHILE USING ARTIFICIAL INTELLIGENCE ON INDEPENDENT LEARNING PROCESSES IN BANJARBARU CITY, SOUTH KALIMANTAN (A CASE STUDY ON THE USE OF CANVA AND CHATGPT) - Mardiana; Muzahid Akbar Hayat; Ahmad Riduan (RADJA PUBLIKA, 2025)
Abstract The development of Artificial Intelligence (AI) technology has had a significant impact on the field of education, particularly in supporting students’ independent learning processes. In this digital era, Senior High School students in Banjarbaru City have begun to utilize AI-based tools, such as ChatGPT and Canva, to assist them in completing assignments and understanding material more efficiently and flexibly. In using AI, students' communication skills play a crucial role in determining the effectiveness of their interactions with the technology, especially in delivering accurate commands or prompts. This research employed a quantitative approach with a correlational method to examine the influence of students’ communication when using AI on their independent learning processes. The data were analyzed using simple linear regression with hypothesis testing (t-test), supported by SPSS version 26. Findings revealed that the t-count was 9.455, with a regression coefficient (β) of 0.221 and a significance level (ρ) of 0.00. These results indicate that the independent learning process variable had a significance value of 0.00 < 0.05, meaning that the independent variable (students’ communication using AI) significantly influenced the dependent variable (independent learning process). The communication variable showed a moderate significant influence of 19.5% on the independent learning process of Senior High School students in Banjarbaru City, as indicated by the R Square value of 0.195. The remaining 80.5% is influenced by other variables not included in this study. Overall, the hypothesis testing confirmed that students’ communication when using AI has a moderate significant effect on their independent learning process.